1997
DOI: 10.1017/s0959270900001714
|View full text |Cite
|
Sign up to set email alerts
|

The world status of the Houbara Bustard Chlamydotis undulata

Abstract: SummaryThe Houbara Bustard Chlamydotis undulata is prominent in avian conservation because of its high value as the traditional quarry of falconers in Arabia and western Asia; such hunting has often been blamed for severely reducing population levels especially in Arabia, Pakistan and Morocco. This paper reviews current knowledge of the world status of the Houbara Bustard in each of the 31 range states where it has occurred within the last 10 years. On the basis of the evidence available, the overall populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
92
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 7 publications
(8 reference statements)
0
92
0
Order By: Relevance
“…Houbara are being trapped on a large scale (4 000-7 000 per year) and smuggled to Middle Eastern countries (Goriup 1997). Mian (1997c) reported annual decline rate of Houbara as high as 18%.…”
Section: Introductionmentioning
confidence: 99%
“…Houbara are being trapped on a large scale (4 000-7 000 per year) and smuggled to Middle Eastern countries (Goriup 1997). Mian (1997c) reported annual decline rate of Houbara as high as 18%.…”
Section: Introductionmentioning
confidence: 99%
“…There are few reliable data on the exact status of houbara bustard populations in the wild but they are generally considered to have declined over most of their range during the last few decades (Collar, 1996;Goriup, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that 4,000-7,000 houbaras are traded annually in this way from Pakistan alone (Goriup, 1997). Mortality of birds transported to the Middle East is high and this trade may have more impact on the status of the houbara bustard than direct hunting with falcons (Bailey et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…There are few reliable data on the exact status of houbara bustard populations in the wild, but they are generally considered to have declined over most of their range during the last few decades for the following reasons: overgrazing, overhunting, agricultural development and human disturbance (Collar, 1996;Goriup, 1997). Although the houbara bustard has been downlisted from Vulnerable to Least Concern in the 1996 Red List of Endangered Animals (IUCN, 1996), a recent review of the world status of the houbara bustard by Goriup (1997) considered that the C. u. macqueenii population should be considered as 'Near Threatened'.…”
Section: Introductionmentioning
confidence: 99%
“…1) where they are used by some falconers to train their falcons. It has been suggested that 4000-7000 houbaras are traded in this way from Pakistan each year (Goriup, 1997), while accurate information on the flow of birds from other countries is unknown. The mortality of the birds transported to the Middle East is high and entire shipments can die after arrival in Gulf countries.…”
Section: Introductionmentioning
confidence: 99%